A Note on Disk Counting in Toric Orbifolds - Chan, Kwokwai; Cho, Cheol-Hyun; Lau, Siu-Cheong; Leung, Naichung Conan; Tseng, Hsian-Hua (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
We compute orbi-disk invariants of compact Gorenstein semi-Fano toric orbifolds by extending the method used for toric Calabi-Yau orbifolds. As a consequence, the orbi-disc potential is analytic over complex numbers.